Business Contract In Contemporary Muamalah Maliyah - Sri Sudiarti (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2016)
This study aims to analyzed contemporary business contract based on muamalah maliyah. The contemporary business contains contract (al-aqd), the term and conditions of contract and its relation with social change. The research method used the library research with the special case study about bay’ al-wafa’. The research results are to anticipate the negative values are conceived and brought about by the social changes in this muamalah issue of Islamic law put forward various principles and rules are used as a benchmark for the validity of a form muamalah created by social change such as bay’ al-wafa’. the fuqaha’ argue that any form of contract there should be objective and will have legal consequences, namely the achievement of the targets. The achievement of the targets will be achieved from the outset of the contract implemented, such as the transfer of ownership from the seller to the buyer.